Implementasi Sistem Informasi Manajemen untuk Peningkatan Kualitas Pelayanan Pendidikan di MTs Muhammadiyah Songing Kabupaten Sinjai - Muallim, Muallim (Universitas Methodist Indonesia, 2025)
This study analyzes the implementation of the Management Information System (MIS) to improve educational services at MTs Muhammadiyah Songing, Sinjai Regency. This qualitative-descriptive research collected data through in-depth interviews with the principal, foundation leader, teachers, and system operator, as well as documentation, which were then analyzed through data reduction, display, and conclusion drawing. The findings indicate that: (1) MIS planning aligns with the school’s vision and mission, focusing on improving service quality and information accuracy; (2) implementation includes managing student data using applications provided by the Ministry of Religious Affairs (EMIS, Verval PD, PD Data, PDUM, RDM) along with ANBK support, which accelerates data input, verification, report generation, and storage; (3) evaluation emphasizes data accuracy, system quality, and timeliness, all of which improved after MIS adoption; and (4) the main supporting factors are stable internet connectivity and the availability of official applications, while the challenges include a still-manual student admission process (PPDB), incomplete data, and the absence of an official school website. The study recommends digitalization and integration of the PPDB system, strengthening data governance, enhancing operator and teacher capacity, and utilizing web and social media channels. The findings underscore the strategic role of MIS in improving service efficiency and the importance of consistent system integration for sustainable impact.